“Shu’ab-i Panjganah” as a Historical Source on the Genealogies of the Chingisids - Sabitov Zh.M. (Золотоордынское обозрение)
Abstract: Research objectives: To analyze “Shu’ab-i Panjganah” as a historical source for the genealogies of the Chingisids. Research materials: Medieval manuscript in the Persian language “Shu’ab-i Panjganah”. The manuscript author is Fazlullah ibn Abulkhair Ali Hamadani Rashid al-Din. The article presents the author’s opinion of all the advantages and disadvantages of the translation of “Shu’ab-i Panjganah”. Results and novelty of the research: “Shu’ab-i Panjganah” is a work of Rashid al-Din, published in 2019. At the beginning of the sixteenth century, this manuscript was in the library of Sultan Qasim of Astrakhan (grandson of Akhmat). There are two versions how this manuscript appeared in Astrakhan. According to the first version (by A. Z. V. Togan), the manuscript was a gift from Muhammad Sheybani to another Astrakhan sultan Qasim (Akhmat’s nephew). According to the second version (by Ch.I. Khamidova) the manuscript appeared in the Golden Horde in the fourteenth century during the campaign of Janibek Khan in Iran. According to the third version (by Zh.M. Sabitov), proposed in this article, the manuscript came to Astrakhan from Herat in the last two decades of the fifteenth century. The children of Akhmat, khan of the Golden Horde, were nephews of Timurid Hussein Baykara (he was the brother of their mother) and for some time they lived in Herat, where they could get a copy of this manuscript. When copying, the scribe made a certain number of minor errors, which is clearly seen when comparing the names of the ancestors, relatives and descendants of Chingis Khan, as well as the Chinghisid emirs with similar names from Jami al-tawarikh and Muizz al Ansab. It is also noted that, without entering into scientific circulation the critical list of Muizz al Ansab on the basis of all five lists, it is not possible to analyze all errors and unique information from “Shu’ab-i Panjganah”.